Quality of life and psychological impact in the photodermatoses: a systematic review. (12th September 2019) - Rutter, K.J.; Ashraf, I.; Cordingley, L.; Rhodes, L.E.
Summary: Background: The photodermatoses affect large proportions of the population but their impact on quality of life (QoL) and psychological health has not been reviewed. Several tools are available to evaluate QoL and psychological impacts. Objectives: To systematically review current literature to identify tools used to assess QoL and psychological impacts in patients with photodermatoses, and to summarize the reported findings. Methods: A systematic search of PubMed, OVID Medline, PsycInfo and CINAHL was performed for articles investigating QoL and/or psychological impact in patients with photodermatoses, published between 1960 and September 2018. Results: Twenty studies were included: 19 incorporated QoL assessment while three evaluated psychological morbidity. Six QoL tools were found to be used: Dermatology Life Quality Index (DLQI), Children's DLQI, Family DLQI, Skindex (16‐ and 29‐item versions), Erythropoietic Protoporphyria Quality of Life (EPP‐QoL) and EuroQol. Between 31% and 39% of photosensitive patients reported a very large impact on QoL (DLQI > 10). Employment and education, social and leisure activities, and clothing choices were particularly affected. Only one tool was specifically designed for a photodermatosis (EPP‐QoL). Four tools were used to evaluate psychological impact: the Hospital Anxiety and Depression Scale, Fear of Negative Evaluation, brief COPE and Illness Perception Questionnaire‐Revised. Levels of anxiety and depression were approximately double British population data. Patients with facial involvement, female gender and younger age at onset showed more psychological morbidity. Conclusions: Several tools have been used to assess QoL in the photodermatoses, and confirm substantial impact on QoL. Development of specific, validated QoL measures would address their unique impacts. Research delineating their psychological comorbidity is sparse and requires further exploration. What's already known about this topic? The photodermatoses negatively impact quality of life (QoL) and cause psychological distress, but no reviews of this area appear in the literature. What does this study add? Few studies have explored the psychological and social impacts of the photodermatoses. There are no fully validated QoL tools specific to the photodermatoses. Around one‐third of adult and child patients with photosensitivity experience very or extremely large impact on QoL, with particular effect on clothing choices, employment and social and leisure activities. Studies suggest anxiety and depression levels in these patients are around double those in the U.K. general population. More attention is required on these 'hidden' conditions. Abstract : Linked Comment: Walburn and Sarkany. Br J Dermatol 2020; 182 :1077 . Plain language summary available online